Development of Capillary Electrophoresis-Based Methods for Analysis of Extracellular Vesicles Isolated from Cancer Cell Lines and Human Saliva - Ren, Lixuan (Université d'Ottawa / University of Ottawa, 2020)
The thesis introduces two developed methods to quantify extracellular vesicles (EVs) isolated from cancer cell lines and healthy human saliva by using capillary zone electrophoresis. In the first chapter, the importance of EVs, as well as the existing EV isolation, characterization, and quantification methods, are described. The general principle of capillary electrophoresis (CE) is explained for a better understanding of these two methods. Chapter II describes the idea and concepts of Extracellular Vesicles quantitative Capillary Electrophoresis (EVqCE). The method evolved from the previous study carried out in our research group for the quantification of viruses. After the isolation of EVs from different cell lines, the characterization and quantification of EVs were performed using nanoparticle tracking analysis (NTA) and flow cytometry. EVqCE consists of four steps for EV quantification. In this study, EVqCE was employed to know the concentrations of EVs in unknown samples, followed by calculation of the average mass of the RNA present in EVs. In the next chapter, one of the human body fluids, i.e., saliva, was chosen for the quantification of EVs. Salivary EVqCE was developed in a similar way as EVqCE for cell lines since the general theories and procedures are practically the same. However, human saliva contains an abundant amount of viscous proteins and ribonuclease (RNase), that were the major obstacles for salivary EVs detection and quantification. The method for the isolation of EVs from the saliva was optimized, and the quantification was performed successfully. The average mass of RNA in saliva EVs was also calculated and analyzed. The concentration of saliva EVs in unknown samples were compared with the results from NTA and flow cytometry to validate the salivary EVqCE. In the last chapter, I described the application of EVqCE to study the quality control of EVs. The method calculates the degradation level of EVs samples under different conditions, providing a potential way for real-time monitoring of the EVs status in the body fluid sample.
Keywords: Extracellular vesicles; Capillary electrophoresis; Cancer cell line; Human saliva